Pelaksanaan Pengabdian Masyarakat Tentang Kejadian Hipertensi Pada Masyarakat Pesisir Di Kelurahan Bintaro Wilayah Kerja Puskesmas Ampenan: Implementation of Community Service Regarding the Incident of Hypertension in Coastal Communities in Bintaro Village, Ampenan Health Center Working Area - Rispawati, Baik Heni; Ernawati; Supriyadi; Riskawaty, Heny Marlina; Halid, Sopian (Chakra Brahmanda Lentera Institute, 2023)
Hypertension is a non-communicable disease that is getting more attention because of hypertension or it is called the silent killer. someone who is said to be hypertensive if the systolic blood pressure is ≥140 mmHg and the diastolic pressure is≥ 90 mmHgThis service activity aims to determine the incidence of hypertension and provide health education to coastal communities in Bintaro village. The method used in this activity is to identify people who have hypertension, then measure blood pressure and provide health education and prevention. With this activity, 80 people who experienced hypertension were found and after being given public health education, they understood and understood hypertension prevention. With this dedication so that people in coastal areas can maintain their diet, lifestyle and further improve their health status by having their health checked more regularly.